The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1051/0004-6361:20042283
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of charged particles by gyroresonant surfing at quasi-parallel shocks

Abstract: Abstract.We discuss an acceleration mechanism of charged particles by magnetohydrodynamic (MHD) structures, such as quasi-parallel shocks and short-large amplitude magnetic structures (SLAMS). In the presence of electromagnetic waves and an electrostatic electric field, particles are accelerated efficiently in the perpendicular direction to the background magnetic field by the combination of two effects, the trapping of particles by the wave and the dragging by the electrostatic field to keep the resonance con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…Such trapping was referred to as "nonresonant trapping" in the past study. 12 Since phase velocities of Alfvén waves with significant wave power are close to Alfvén speed ͑V A =1͒, ions are mainly scattered in the v ix − ͉v iЌ ͉ phase space keeping ͑v ix −1͒ 2 + ͉v iЌ ͉ 2 = V 2 = const due to the nonresonant pitch angle scattering. The approximate trapping region is given by the first integral of equation of individual ions 11,12 H = − ͉b͉ ͱ 1 − 2 cos +…”
Section: B Time Evolution Of the Vdfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such trapping was referred to as "nonresonant trapping" in the past study. 12 Since phase velocities of Alfvén waves with significant wave power are close to Alfvén speed ͑V A =1͒, ions are mainly scattered in the v ix − ͉v iЌ ͉ phase space keeping ͑v ix −1͒ 2 + ͉v iЌ ͉ 2 = V 2 = const due to the nonresonant pitch angle scattering. The approximate trapping region is given by the first integral of equation of individual ions 11,12 H = − ͉b͉ ͱ 1 − 2 cos +…”
Section: B Time Evolution Of the Vdfsmentioning
confidence: 99%
“…Recent studies using test particle simulations 6,7,9 and quasilinear theories 8,10 have also demonstrated that the nonresonant scattering by finite-amplitude Alfvén waves 11,12 leads to the perpendicular "pseudoheating" of ions, without dissipation of wave energy. 7,8 Araneda et al 3 have recently proposed an interesting scenario for generating a beam proton distribution when large amplitude Alfvén waves are present.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism proposed here can act alone and/or in combination with some other phenomena like shocks that are also known to accelerate particles (Sandroos & Vainio 2009;Kuramitsu & Krasnoselskikh 2005;Aran et al 2007). Together, the two phenomena may transport particles to high altitudes and provide physical explanation for the observations of solar energetic particles at high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, nonlinear motion of a single particle in a one-dimensional space has been analyzed based on the Hamiltonian for the particle motion (e.g., Kuramitsu and Krasnoselskikh, 2005). In the presence of finite amplitude MHD wave with a single mode, the corresponding Hamiltonian can be described as a time-independent function in phase space coordinates which are pitch angle cosine in the wave rest frame µ and phase ψ between transverse magnetic field fluctuation and transverse velocity vectors.…”
Section: Single Particle Motionmentioning
confidence: 99%